Pabstiella hileiaensis (Orchidaceae Pleurothallidinae), a new species from the Atlantic Rainforest in southern Bahia, Brazil - Gutiérrez Morales, Nicolás; Toscano De Brito, A. L. V.; Smidt, Eric De Camargo (Phytotaxa, 2021)
Distributed along the eastern coast of South America and considered one of the world’s biological hotspots, the Atlantic Rainforest harbors outstanding levels of richness and endemism (Myers et al. 2000). Specifically, with 14,847 vascular plant species (Reginato & Michelangeli 2020), including 1,480 (1,100 endemics) belonging to the Orchidaceae (BFG, 2015), this biome is considered a priority for plant and orchid conservation in the Neotropics since more than 88% of its pre-Columbian area is already lost (Peres et al. 2020).